Regionalised Mobility Management For Mobile IP - Tan, Wee Lum (1999)
This thesis presents a regionalised mobility management approach to Mobile IP to solve several inherent problems in the Mobile IP base protocol. The Mobile IP protocol as specified in RFC2002[Perkins, 1996b] provides a scalable mechanism for node mobility within the Internet. However, there still exist several outstanding issues related to efficient mobility management, handoff, key management, support for private address spaces and the inefficient routing of data to a mobile node. Firstly , Mobile IP does not perform well when dealing with large numbers of mobile nodes moving frequently across small wireless subnets. Mobile nodes that move in this way suffer periods of service disruption due to the delay incurred in determining the movement across the boundary of a subnet and later updating their new location information with their possibly distant home agents. Secondly, key management between the mobile node and the foreign agent, and between both the foreign and the home agents raises scalability issue. Thirdly, Mobile IP assumes that the foreign agent an dthe home agent can interact directly during the registration process. This assumption leads to operational problems when either or both the agents are located on private networks, using private IP addresses. Finally , in Mobile IP, any datagrams from a correspondent node to the mobile node must pass through the home agent, creating an inefficient triangular routing of the datagrams. In this thesis, a study is made on an approach known as DREMIP [Chuah & Li, 1997] which intriduces some extensions to the Mobile Ip base protocol to provide a more scalable solution to the mobility management problem. This approach employs a hierarchical system, with a home domain at the top, a foreign domain below it, and the foreign networks in foreign domain at the bottom of the hierarchy. DREMIP also separates the registration and forwarding services provided by the mobility agents in RFC2002. The registration service can be provided by a new network entity called registration server while the forwarding service can be provided by another new network entitycalled care-of agents. DREMIP operates on the assumption that user mobility is more common between adjacent cells or network in the same routing domain. Thus, local mobility is handled without involving the home domain. Control traffic generated by local handoffs is confined to within the local routing domain, which will improve handoff performance by reducing the registration latency and the frequency of distant registrations with the home agent. In this thesis, DREMIP is implemented in the Linux OS and several handoff experiments are conducted on a wireless testbed. The handoff experiment results show that the DREMIP approach produces a handoff performance that is significantly better compared to the Mobile IP base protocol approach. In addition, enhancements are also made to the mobile node to provide it with the capability to measure and compare the signal strengths of multiple foreign agents in an overlapped region of coverage. With this capability , a better-informed mobile node will be able to make the right decision about when to handoff to a new agent. This enhancement results in a vastly improved handoff performance compared to the handoff performance of the standard DREMIP and Mobile IP approaches. DREMIP's introduction of a registration server in each administrative routing domain enables the home domain to maintain just one security association with the entire foreign domain, instead of maintaining individual security associations with each specific foreign agent in the foreign domain. Thus, this eases the key management problem as well as enhances the scalability of the DREMIP model. Furthermore, by locating the registration servers and care-of agents on the border of their domain, DREMIP is able to provide support for private address spaces. In this thesis, route optimisation [ Perkins & Johnson, 1997b ] extensions are also applied to DREMIP so that the triangular routing of datagrams is eliminated. With route optimisation, correspondent nodes can send datagrams diretly to a mobile node's current location, bypassing the route through the mobile node's home network. Experiments are also conducted to measure the TCPP throughput performance of a DREMIP model enhanced with the route optimisation feature, and the results show significant improvement compared to the TCP throughput performance of a standard DREMIP model without the route optimisation feature. Finally, this thesis also discusses other capabilities of DREMIP that can be utilised to provide support for multicasting, QoS ( quality of service), AAA( authentication, authorisation and accounting) and load balancing features. The interoperability feature of DREMIP is also described. This feature allows the mobile nodes and mobility agents in a DREMIP model to interoperate with mobile nodes and mobility agents supporting the Mobile IP base protocol specified in RFC2002. Several handoff and interoperability tests are conducted on a wireless testbed set up in the Faculty and the results verify the interoperability feature as well as the proper operation of the DREMIP implementation.